3 root 2 -2 root 3. ========– + 3 root 2 +2 root 3 3 root 2 + 2root 3 =======

Question

3 root 2 -2 root 3.
————————– +
3 root 2 +2 root 3
3 root 2 + 2root 3
—————————
3 root 2 – 2 root 3. Simplyfy

in progress 0
Ivy 2 months 2021-10-04T21:49:27+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-10-04T21:51:03+00:00

    Answer:

    10 is the answer mate

    Step-by-step explanation:

    follow me and mark this the brainliest

    0
    2021-10-04T21:51:12+00:00

    answer is 10…..

    ……

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )